2021
DOI: 10.1093/brain/awab219
|View full text |Cite
|
Sign up to set email alerts
|

KCNT1-related epilepsies and epileptic encephalopathies: phenotypic and mutational spectrum

Abstract: Variants in KCNT1, encoding a sodium-gated potassium channel (subfamily T member 1), have been associated with a spectrum of epilepsies and neurodevelopmental disorders. These range from familial autosomal dominant or sporadic sleep-related hypermotor epilepsy ((AD)SHE) to epilepsy of infancy with migrating focal seizures (EIMFS) and include developmental and epileptic encephalopathies (DEE). This study aims to provide a comprehensive overview of the phenotypic and genotypic spectrum of KCNT1 mutation-related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
91
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(94 citation statements)
references
References 36 publications
(52 reference statements)
2
91
1
Order By: Relevance
“…The limitation of delayed genetic confirmation appears to be more prominent for KCNT1 -related epilepsies. A recent publication by Bonardi et al [ 14 ], summarizing 248 cases of KCNT1 -related epilepsy, reported lower ages of seizure onset than the ages at diagnosis of KCNT1 patients reported in our study. The calculated incidence is therefore likely an overestimate that includes prevalent cases which were incident before the discovery of the KCNT1 gene but only genetically confirmed during the study period, as well as familial ADSHE cases that were diagnosed after one member (i.e., the proband) was diagnosed ( Section 4.4 ).…”
Section: Discussioncontrasting
confidence: 72%
See 3 more Smart Citations
“…The limitation of delayed genetic confirmation appears to be more prominent for KCNT1 -related epilepsies. A recent publication by Bonardi et al [ 14 ], summarizing 248 cases of KCNT1 -related epilepsy, reported lower ages of seizure onset than the ages at diagnosis of KCNT1 patients reported in our study. The calculated incidence is therefore likely an overestimate that includes prevalent cases which were incident before the discovery of the KCNT1 gene but only genetically confirmed during the study period, as well as familial ADSHE cases that were diagnosed after one member (i.e., the proband) was diagnosed ( Section 4.4 ).…”
Section: Discussioncontrasting
confidence: 72%
“…The calculated incidence is therefore likely an overestimate that includes prevalent cases which were incident before the discovery of the KCNT1 gene but only genetically confirmed during the study period, as well as familial ADSHE cases that were diagnosed after one member (i.e., the proband) was diagnosed ( Section 4.4 ). Notably, the phenotypes included in the Bonardi et al study [ 14 ] largely consisted of EIMFS, which tend to be sporadic and not familial, while in our study ADSHE was the most common phenotype. Compared with EIMFS, ADSHE cases tend to be less severe in the prognosis and are associated with longer survival.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…With the development of high-throughput sequencing technology, opportunities have been provided to investigate the underlying molecular-genetic basis of epilepsy. More than 100 genes have been identified to be related to EOEE, such as cdc42 guanine nucleotide exchange factor 9 [arHGeF9; online Mendelian inheritance in Man (oMiM) #300607], cyclin-dependent kinase-like 5 (cdKl5; oMiM #300203), potassium sodium-activated channel subfamily T member 1 (KcnT1; oMiM #614959), sodium voltage-gated channel α subunit 8 (Scn8a; oMiM #614558), solute carrier family 2 member 1 (Slc2a1; oMiM #614847) syntaxin-binding protein 1 (STXBP1; oMiM #602926), polynucleotide kinase 3'-phosphatase (PnKP; oMiM #605610) and potassium voltage-gated channel subfamily Q member 2 (KcnQ2; oMiM #602235) (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). among these, KcnQ2 is the causative gene for 7-10% of cases of eoee (15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%